Simplify : (3+√5)(3-√5)
Answers
Answered by
42
→
We know that →
- (a + b)(a + b) = a² - b²
Mark as Brainliest !! ✨✨
Answered by
4
(3 + √5)(3 - √5) = 4
Given :
The expression (3 + √5)(3 - √5)
To find :
To simplify the expression
Solution :
Step 1 of 2 :
Write down the given expression
The given expression is
(3 + √5)(3 - √5)
Step 2 of 2 :
Simplify the given expression
━━━━━━━━━━━━━━━━
Learn more from Brainly :-
If x=√3a+2b + √3a-2b / √3a+2b - √3a-2b
prove that bx²-3ax+b=0
https://brainly.in/question/19664646
2. the order of the surd 7√8
https://brainly.in/question/31962770
Similar questions